Pushing down on me: The paradoxical role of self-leadership in the context of work pressure - Christopher B. Neck; Christopher P. Neck; Elizabeth A. Goldsby; Michael G. Goldsby (Administrative Sciences, 2023)
One of the most pressing threats to individual employees in today's fast-paced work environment is work pressure. In this paper, the intention is to link the individual influence process of self-leadership to work pressure, representing the first empirical research to do so. Through this linkage, we suggest a means by which the individual worker may deal with the external force of work pressure, thus decoupling the consequences of work pressure from the organizational influence. Through linking self-leadership to work pressure's effects, we examine how the individual may mitigate the negative work pressure-driven outcomes whereas past research has typically focused on what the organization may do to mitigate these effects. Finally, this study aims to disentangle an existing paradox in the self-leadership literature through examining how the various strategies of self-leadership perform differently under the context of work pressure.
Keywords: 350; occupational stress; stress; time pressure; work pressure